Effects of Community Participation on School Infrastructure Development in Rural Uganda - Ngwama, Christine (African Journal of Education and Practice, 2024)
Purpose: The aim of the study was to investigate the effects of community participation on school infrastructure development in rural Uganda. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Community participation in rural Uganda positively impacts school infrastructure development by fostering ownership and ensuring cultural relevance. Local contributions reduce costs and speed up construction, though variable participation and limited skills can pose challenges. Strong community engagement is essential for the success and sustainability of these projects. Unique Contribution to Theory, Practice and Policy: Social capital theory, stakeholder theory & asset-based community development (ABCD) theory may be used to anchor future studies on the effects of community participation on school infrastructure development in rural Uganda. Establish regular feedback mechanisms through community meetings, surveys, and online platforms. Governments and educational authorities should formulate policies that support and mandate community involvement in all phases of school infrastructure development.